2016
DOI: 10.1055/s-0035-1570352
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning/Track-and-Trigger Systems to Detect Deterioration and Improve Outcomes in Hospitalized Patients

Abstract: As a global effort toward improving patient safety, a specific area of focus has been the early recognition and rapid intervention in deteriorating ward patients. This focus on "failure to rescue" has led to the construction of early warning/track-and-trigger systems. In this review article, we present a description of the data behind the creation and implementation of such systems, including multiple algorithms and strategies for deployment. Additionally, the strengths and weaknesses of the various systems an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 42 publications
(52 reference statements)
0
24
0
Order By: Relevance
“…Research has demonstrated that measurable physiological changes occur in patients up to 48 hours before cardiopulmonary arrest (Shiloh, Lominadze, Gong, & Savel, 2016). There are "objective parameters" that, when examined in a trending manner, can predict "physiological dysfunction" (Howard, 2016, p. 14).…”
Section: Failure To Rescuementioning
confidence: 99%
“…Research has demonstrated that measurable physiological changes occur in patients up to 48 hours before cardiopulmonary arrest (Shiloh, Lominadze, Gong, & Savel, 2016). There are "objective parameters" that, when examined in a trending manner, can predict "physiological dysfunction" (Howard, 2016, p. 14).…”
Section: Failure To Rescuementioning
confidence: 99%
“…There are systems that help nurses to know when to escalate care and also detect changes prior to deterioration, such as early warning scores (EWS), also known as Track and Trigger Systems (TTS) [8,10,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple parameter systems are expanded versions of the single parameter ones, using a combination of abnormal signs to trigger a response. The aggregate weighted systems assign points to the degree of deviation of individual physiological variables, combining them to a score, which has thresholds for triggering [19]. In addition, many systems include the facility for triggering on a subjective basis, recognizing the importance of clinical intuition in patient assessment [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the IOM and the Institute for Healthcare Improvement (IHI) have called for error-proofing of healthcare delivery systems to ensure early identification of potential adverse events [16,17,18]. Electronic health record (EHR)-based trigger tools have been successful in identifying potential risk of patient harm and improving intervention timeliness [1,19,20,21,22,23,24]. However, little is known about trigger tools embedded within patient- or family-reported outcome systems.…”
Section: Introductionmentioning
confidence: 99%